The study of human resource management in Chinese SMEs - Guo, Zhenzhong; Bi, Chuanchen (Technium Social Sciences Journal, 2024)
With the rapid development of China's economy, small and medium-sized enterprises (SMEs) play an important role in promoting national economic growth, creating job opportunities and promoting technological innovation. However, at present, there are many problems in human resource management in China's SMEs, which limit their development potential and competitiveness, such as the lagging management concept, imperfect training mechanism and high employee turnover rate in human resource management. This paper puts forward the corresponding solutions, such as establishing the people-oriented management concept, increasing the training input, optimizing the salary and welfare system and establishing a good promotion mechanism. At the same time, SMEs should adjust and optimize according to their actual conditions to ensure that these strategies can effectively improve the level of human resource management and provide support for the sustainable development of enterprises.